TEKNIK PENENTUAN LOKASI GIGI MOLAR TIGA RAHANG BAWAH IMPAKSI - Evy Savitri; Achmad Alhamid (Faculty of Dentistry, Universitas Indonesia, 2015)
Impacted third mandibular molar seems as a common and easy case but actually a difficult one when the odontectomy proceeds. Besides, another unpredicted problems often appear such as fractured tip, traumatized and damaged of the madibular canal. To decide the odontectomy procedure, a dentist has to do the examination systematically. In this case, radiographic examination is very important to perceive the location as well as the shape of the third molar, especially its position to the adjacent anatomic structure that has to be considered during operation. This whole view will help dentist to decide appropriate approach. A special radiographic examination enables dentist to predict the treatment result more accurately, since the location and shape of the tooth currently perceived. With this more complete diagnostic information, an appropriate treatment plan could be arranged and unfacorable risk could be limited, therefore complication and failure could be avoided.